Malaysia on the right track to a develop nation speeches of Prime Minister Najib Tun Razak, 2014 - Najib Tun Razak; Ku Azian Ku Azizan (Jabatan Penerangan Malaysia, 2015)
Speeches of Malaysia's Prime Minister, Datuk Seri Najib Tun Razak.